A NOVEL BACTERIA RECOVERED FROM CASES OF SUBCLINICAL MASTITIS IN EWES - saleem amin Hasso (Basrah Journal of Veterinary Research)
Four hundred milk samples were collected from 205 local breed ewes for the detection of clinical and sub clinical mastitis. The incidenceof clinical mastitis ' was (7.25%) while that of sub clinical mastitis was (26.25%). I-Iistophilus Ovis was isolated from natural cases of sub clinical mastitis of ewes and is a novel bacterium A to Iraqi mastitis literature